1979
DOI: 10.1007/bf01982976
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sensitivity to pyrazophos of cucumber and gherkin powdery mildew

Abstract: In some cucumber and gherkin greenhouses in the Netherlands, where Curamil (a.i. pyrazophos) had been used for control of powdery mildew, unsatisfactory disease control was obtained in recent years. Laboratory tests revealed a decreased sensitivity of the pathogen to the fungicide. The fitness and the competitive ability of pyrazophos resistant strains in absence of the fungicide appeared to be somewhat lower than that of the normal, sensitive strains. The implications with respect to disease control in practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…This genetic plasticity has now been extended to include fungicide resistant strains. Strains resistant to the four major groups of systemic (specific site inhibitor) fungicides were reported within a few years of field use (Bent et al 1971;Peterson 1973;Dekker & Gielink 1979;Schepers 1983). In addition, studies by Schepers (1984Schepers ( , 1985 showed resistance to benzimidazole, hydroxypyrimidine, and organophosphate fungicides was persistent over several years even with little or no selection pressure and DMI resistant isolates were competitive with sensitive isolates.…”
Section: Discussionmentioning
confidence: 99%
“…This genetic plasticity has now been extended to include fungicide resistant strains. Strains resistant to the four major groups of systemic (specific site inhibitor) fungicides were reported within a few years of field use (Bent et al 1971;Peterson 1973;Dekker & Gielink 1979;Schepers 1983). In addition, studies by Schepers (1984Schepers ( , 1985 showed resistance to benzimidazole, hydroxypyrimidine, and organophosphate fungicides was persistent over several years even with little or no selection pressure and DMI resistant isolates were competitive with sensitive isolates.…”
Section: Discussionmentioning
confidence: 99%
“…Two R isolates gradually disappeared from the population, but two others competed well with the wild-type isolate $6. A reduction in the number of R conidia in a similar experiment was observed in S. fuliginea isolates resistant to benzimidazoles (Zadoks, 1982) and pyrazophos (Dekker and Gielink, 1979). It can be attributed to a weaker competitive ability of the R isolates under such circumstances.…”
Section: Stability Of Resistancementioning
confidence: 49%
“…The density of conidia administered was so high that only some of them could develop (Hollomon, 1978;Dekker and Gielink, 1979;Zadoks, 1982). This type of competition experiment corresponds with the type I experiment.…”
Section: Stability Of Resistancementioning
confidence: 98%
“…oryzae have a relatively low rate of in vitro growth and degree of sporulation indicating decreased fitness. Fitness and competitive ability of pyrazophos-resistant strains of S. fuliginea also appeared to be somewhat reduced (Dekker and Gielink, 1979). This might implicate that under field conditions emergence of resistance to pyrazophos only may occur at a high and continuous selection pressure of the fungicide.…”
Section: Discussionmentioning
confidence: 93%
“…Resistance to pyrazophos has also been found in Sphaerothecafuliginea (Dekker and Gielink, 1979) and to other organophosphorus fungicides such as IBP and edifenphos in P. oryzae (cf. Uesugi, 1978).…”
Section: Discussionmentioning
confidence: 98%